The last man standing is a woman a gendered analysis of the media coverage of Senator Risa Hontiveros from the 17th to the 19th Congress in selected online news outlets - Abella, Czashaine Mai T.; Javier, Angelica Monique C.
Grounded in framing theory, feminist media studies, and liberal feminism, this study analyzes how Inquirer.net, Philstar.com, and Rappler framed Senator Risa Hontiveros from the 17th to the 19th Congress, using 1,456 sampled news articles. Through the indicators of tone, visibility, and presence of gender bias, it analyzes the progression of Hontiveros’ media representation over time. Findings reveal distinct editorial tendencies: Inquirer.net shifted from a neutral to a supportive tone; Philstar.com maintained a consistently neutral stance; and Rappler showed a more dynamic trajectory, becoming increasingly supportive in tone. Visibility was examined through the presence of Hontiveros’ name in headlines, her order of appearance in articles, and the number of times she was quoted. Results show consistently low headline visibility across all outlets and time periods, but high visibility in terms of order of appearance and frequency of quotations in articles where she was directly tagged. The presence of other frequently quoted individuals provided further context for the coverage. In terms of gendered representation, the study found minimal use of stereotypical images across all platforms, with coverage generally focused on Hontiveros’ legislative work and advocacies. However, even the limited instances of stereotypical framing suggest the persistence of subtle gender biases in news narratives.